Effect of Numerical Requirement System on Dental Students’ Learning Strategies - Handayani, Fani T.; Claramita, Mora; Rahayu, Gandes R. (Journal of Dentistry Indonesia, 2015)
Research on the impacts of the ‘requirement system’ on student learning is still rare, however the system is still widely applied by Dental Schools in many countries. The major consequent of this system is the unpreparedness of students’ learning prior to presenting patients with particular complaints. Objective: This study aimed to explore the effect of the ‘requirement system’ on students’ learning strategy in Dental Education University of Jenderal Soedirman, Purwokerto, Indonesia. Methods: This was a qualitative-phenomenography study. The collection of data was through observations and interviews. The number of subjects was 13 students of the same batch in a clinical education level, determined by purposive sampling. Observations by 2 clinical teachers were done in advance and lasted for six weeks, followed by in-depth interviews. The analysis followed the phenomenography method. Results: Interviews revealed that application of the ‘requirement system’ had prompted the students to get the patients and to learn or not learn correspondingly to the specified cases. Students will have adequate preparation to learn if they are motivated to discuss with the teachers, having previous experiences, and if the patient is perceived to be special. Inadequate preparation of learning occurred when students felt tired, insufficient time between patients’ arrival and presentation in front of clinical teachers, and repetition of the case. Observations revealed that preparation for learning did not consequently lead to students’ performance in doing clinical work. ‘Well-done’ up to ‘less than expected’ performances were found in both single-cases as well repetition-cases. Conclusion: ‘Requirement system’ driven students’ preparation for learning. However, number of cases did not. Modifying the ‘requirement system’ and improving the quality of clinical supervision are two important things suggested by this study